Exploring White individuals' perceptions of Black atheists' trustworthiness, racial identity, and feelings of warmth. (16th February 2022) - Howard, Simon
Abstract : Anti‐atheist bias in the United States is both persistent and pervasive. However, most experimental psychological research demonstrating anti‐atheist bias have used White targets or targets whose race is not explicitly mentioned. Thus, it is unknown whether atheists of colour, who have two stigmatised identities (e.g., their race and atheist identification), are perceived differently from their ingroup counterparts with one stigmatised identity (e.g., Black Christian). Using a between‐subjects experimental design we examined White Americans' ( n  = 286; M age  = 39.91, SD  = 13.17) perceptions of Black atheists' trustworthiness and racial identification relative to Black non‐atheists. We also explored whether exposure to Black atheists versus Black Christians would influence White individuals' feelings of warmth towards Black Americans in general. There was no evidence that White individuals perceive Black atheists as less trustworthy or less racially identified than non‐atheist Black individuals (i.e., Black Christians and Black individuals whose religious identity was not explicitly mentioned). Results did reveal, however, that White individuals had higher feelings of warmth towards Black Americans in general (and several other stigmatised groups) after exposure to a Black Christian versus Black individuals who were not Christian. Implications and future research directions are discussed, particularly focused on atheists who are multiply stigmatised.